2017
DOI: 10.1073/pnas.1700759114
|View full text |Cite
|
Sign up to set email alerts
|

Mutational spectra of aflatoxin B 1 in vivo establish biomarkers of exposure for human hepatocellular carcinoma

Abstract: Aflatoxin B 1 (AFB 1 ) and/or hepatitis B and C viruses are risk factors for human hepatocellular carcinoma (HCC). Available evidence supports the interpretation that formation of AFB 1 -DNA adducts in hepatocytes seeds a population of mutations, mainly G:C→T:A, and viral processes synergize to accelerate tumorigenesis, perhaps via inflammation. Responding to a need for early-onset evidence predicting disease development, highly accurate duplex sequencing was used to monitor acquisition of high-resolution muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
113
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(125 citation statements)
references
References 43 publications
10
113
0
1
Order By: Relevance
“…5B,C; Supplemental Table S2). We also note that the signature of AFB1 mutagenesis, inferred from 397 mutations in 6.4 kb of sequence in AFB1-exposed mice (Chawanthayatham et al 2017), is similar to the AFB1sig G>N reported here (cosine similarity 0.96; Chawanthayatham and colleagues show mutation frequencies per trinucleotide; for comparison, the right hand side of Fig. 6A shows AFB1sig G>N using the same conventions).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…5B,C; Supplemental Table S2). We also note that the signature of AFB1 mutagenesis, inferred from 397 mutations in 6.4 kb of sequence in AFB1-exposed mice (Chawanthayatham et al 2017), is similar to the AFB1sig G>N reported here (cosine similarity 0.96; Chawanthayatham and colleagues show mutation frequencies per trinucleotide; for comparison, the right hand side of Fig. 6A shows AFB1sig G>N using the same conventions).…”
Section: Discussionsupporting
confidence: 80%
“…Aflatoxin exposure is thought to be a major public health risk in parts of Africa and Asia, partly by synergizing with hepatitis B to dramatically increase risk of hepatocellular carcinoma (HCC) (Kensler et al 2003; IARC Working Group on the Evaluation of Carcinogenic Risks to Humans 2012). However, to our knowledge, the extended mutational signatures of aflatoxins have been little-studied in the context of normal metazoan DNA repair: a study in Caenorhabditis elegans examined the AFB1 mutation signature based on 31 single base-substitution mutations (Meier et al 2014), and ultradeep sequencing of 6.4 kilobases (kb) in AFB1-exposed mice inferred an AFB1 signature from 397 mutations (Chawanthayatham et al 2017).…”
mentioning
confidence: 99%
“…While no studies explicitly have assessed the dose/duration of exposure parameters of PQ induction of genetic disease, we have recently provided an animal model (the B6C3F1 gpt delta mouse) in which that hypothesis can be tested in a future study. The B6C3F1 gpt delta mouse carries 80 copies of the gpt gene integrated into its DNA, which enables a very accurate measurement of the in vivo mutagenic effects of environmental agents [49]. …”
Section: Discussionmentioning
confidence: 99%
“…Using this model, we have established that PQ is mutagenic and cytotoxic, its properties stemming from its ability to generate ROS and induce genomic accumulation of oxidative DNA lesions such as 8OG. The system described is well poised to enable deeper analysis of PQ mutagenesis in terms of the specific types of point mutations induced, and mutational spectra, both in the AS52 cells, and in an animal model (e.g., B6C3F1 gpt delta mouse [34, 49]).…”
Section: Discussionmentioning
confidence: 99%
“…public health. Its properties, toxic to humans, have a broad spectrum, with special attention to the carcinogenic effects (Ross et al, 1992;Chawanthayatham et al, 2017). AFM1 is allocated to the human carcinogenic group 1 by the International Agency for Research on Cancer (Bosch & Peers, 1991;IARC, 2012;Ostry et al, 2017).…”
Section: Introductionmentioning
confidence: 99%